The origin of visible light absorption in chalcogen element (S, Se, and Te)-doped anatase TiO2 photocatalysts - Dong, Zhili (2011)
We use first-principles calculations to clarify the origin of the visible light absorption in chalcogen element-doped TiO2. Our results show that interstitial doping is not the origin of visible light absorption under any equilibrium growth conditions, but rather, sensitization is achievable via substitutional doping of O (or Ti) at Ti-rich (or O-rich) conditions, respectively. With increasing atomic number (from S to Te), it is harder to form anion-doped TiO2 but easier to achieve cationic doping. Both anionic and cationic doping can confer visible light absorption, but the former is more effective. The effect increases with increasing atomic number of the chalcogen element. Dopant pairing is found in anionic S-, Se-, and Te- and cationic S-doped TiO2. We further identified that anion pairing induces a bathochromic shift in the absorption, whereas cationic pairing causes the opposite, that is, a hypsochromic (blue) shift, predictions that agree well with the experimental findings.